Proceedings of the 4th Asia-Pacific Bioinformatics Conference : (Imperial College Press, 2006)
High-throughput sequencing and functional genomics technologies have given us a draft human genome sequence and have enabled large-scale genotyping and gene expression profiling of human populations. Databases containing large numbers of sequences, polymorphisms, and gene expression profiles of normal and diseased tissues in different clinical states are rapidly being generated for human and model organisms. Bioinformatics is thus rapidly growing in importance in the annotation of genomic sequences, in the understanding of the interplay between genes and proteins, in the analysis of the genetic variability of species, and so on. This proceedings contains an up-to-date exchange of knowledge, ideas, and solutions to conceptual and practical issues of bioinformatics, by researchers, professionals, and industrial practitioners at the 4th Asia-Pacific Bioinformatics Conference held in Taipei in February 2006.